Ignorantia juris non excusat: The trial and the affirmation of the Italian legal thriller. (August 2019) - Bratos, Francesco
The complex relationship between literature and law has been widely debated. Over the last 20 years, the judicial novel has been the subject of renewed consideration from critics. Numerous studies have pointed out how literary and judicial practices seem characterized by common methods of narrative organization and communication of experiences. Beyond the controversy on the classification of the judicial novel as literary genre, the representation of courtrooms has undeniably become one of the recurring tropes of the 20th-century novel. Within this multifaceted literary movement, the unique style of Italian judiciary literature warrants its articulation as a distinct genre. The working hypothesis of this article is that the political and cultural centrality acquired by the Italian Magistratura, as result of a longstanding confrontation with the political powers, is essential in studying the success of the Italian judiciary novel, together with the emergence of a vast number of jurist-writers. Analyzing specifically the work of the jurist-writer Gianrico Carofiglio, I will demonstrate how the Italian legal thriller transforms the representation of the trial, dealing with the literary tradition as well as with law's own representation.